Communication Pattern of Wilayatul Hisbah, Lhokseumawe City in Implementing Amar Makruf Nahi Mungkar - Hasbullah Hasbullah; Mohd Hatta; Zainal Arifin (Budapest International Research and Critics University, 2018)
Communication is the process of delivering messages by someone to other people to tell, change attitudes, opinions or behavior either directly orally or indirectly through the media. In this communication requires a reciprocal relationship between the delivery of messages and recipients namely communicators and communicants. The purpose of Islamic communication is to give good news with the shadow of the multiplication of fahala and the recompense of heaven, giving news of fear of the threat of doom, and the reward of hell. And invite the people to understand and forbid from evil deeds, and remind those who are negligent, and teach and guide those who are ignorant. The type of research contained in this dissertation is qualitative. Qualitative research is a study that aims to understand the phenomena or social realities that arise in society which are subject to holistic research, and by describing in the form of words and languages in a special context that is natural by utilizing various natural methods. The approach that the researchers used in this study was case studies. In this study, researchers explored the patterns of communication carried out by members and institutions of the Wilayatul Hisbah in implementing amar ma'ruf nahi munkar in Lhokseumawe City.